Hei whare onerua : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters in Māori Visual Arts at Massey University, Te Papaioea, Aotearoa - Bentley, Java (Massey University, 2024)
Hei whare onerua speaks to compost in relation to the cyclic nature of all things within a whare onerua context. Onerua relates to hangarua, as the second life of soil or oneone. Firstly, this exegesis investigates mana wāhine through the relationship between tangata and Papatūānuku. Secondly, pūrakau and the innovation of ringatoi Māori present new ways of approaching kaitiakitanga in relation to Te Taiao. Therefore, presenting whakapapa and the provenance of all materials is crucial in demonstrating the reciprocal cycle of giving and receiving. By developing the relationship between people and the land, the connection to the whenua is central in sustaining a sense of belonging. Onerua does not exist in isolation but binds tangata whenua and thus a shared sense of belonging to the land and one another. The making of compost is inherently collaborative. This kaupapa was the preparation of onerua as a site-specific project to the Cubeside Annex thus providing a kāinga rua for creatives studying Māori Visual Arts based at Te Pūtahi-a-Toi in Te Papaioea. From the framework of reciprocity, this kaupapa honours the creatives who have paved the way for future generations and as a gift, the onerua represents the return of new mauri back to the Cubeside Annex.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)